Creation of an electronic trilingual dictionary of biological terms with linguoculturological components - Kalizhanova, A.; Maryshkina, T.; Ishmuratova, M.; Gruzina, Y.; Ibrayeva, В. (Opción, 2020)
Digitization of educational system of the Republic of Kazakhstan, coupled with the Trilingualism program, has revealed the problem of the lack of trilingual training and resource books and, as a result, their mass creation in electronic form. This article deals with the experience of creating a disk version of an electronic trilingual dictionary of biological terms with a linguoculturological component using the Adobe Dreamweaver program. The experience of application and use based on a survey of teachers suggests that Adobe Dreamweaver is ideal for visualizing the linguoculturological component of the term in order to effectively memorize the latter. © 2020, Universidad del Zulia. All rights reserved.
Keywords: electronic trilingual dictionary; linguistic and cultural component; cognitive skills; Adobe Dreamweaver; visualization